POTENSI FLORA TANAMAN HIAS SEBAGAI ODTWA JALUR PATROLI AIR TERJUN GUHUNG ELANG RESORT BELABAN TAMAN NASIONAL BUKIT BAKA BUKIT RAYA - Siahaan, Sarma; Wulandari, Reine Suci; Mangurai, Silvia Uthari Nuzaverra Mayang; Arianto, Arianto (JURNAL HUTAN LESTARI, 2024)
Bukit Baka Bukit Raya National Park is a conservation area that is rich in biodiversity, including ornamental plant flora. The potential of this flora has not been fully exploited as a natural tourist attraction in the region, especially on the Guhung Elang Resort Belaban Waterfall patrol route Belaban Region-1. Ornamental plants are one of the potential objects to attract the attention of tourists because of their visual beauty and ecological value which helps strengthen environmental sustainability. This research aims to explore the potential of ornamental plant flora as a natural tourist attraction on the Guhung Elang Resort Belaban Waterfall Patrol Route Region-1 Bukit Baka Bukit Raya National Park. The research used a survey method to explore the diversity of ornamental plant flora around the tourist area. The starting point of the route is at the Belaban resort office information center. There are 2 observation routes, namely route 1 (Guhung Elang patrol route Km 37) and route 2 (Semunga waterfall route Km 35). Research parameters are plant type, coordinate points, distance and travel time. The results of the research found that there were potential ornamental plants in 20 families on both routes, with a total of 94 individuals. In route 1 there were 44 individuals, while in route 2 there were 50 individuals. The most common types of ornamental plants are orchids, senthe/ keladi, and nampu/murau. The discovery of the potential for ornamental plant flora provides an opportunity for the development of natural tourism in the area by working on the visual beauty and ecological value of ornamental plants, which can attract tourists to visit this location. The discovery of the potential for ornamental plant flora provides an opportunity for the development of natural tourism in the area by working on the visual beauty and ecological value of ornamental plants, which can attract tourists to visit this location.Keywords: Flora, Guhung Elang, Ornamental Plants, PotencyAbstrakTaman Nasional Bukit Baka Bukit Raya merupakan salah satu kawasan konservasi yang kaya akan keanekaragaman hayati, termasuk flora tanaman hias. Potensi flora ini belum dimanfaatkan sepenuhnya sebagai objek daya tarik wisata alam di wilayah tersebut, terutama di jalur patroli Air Terjun Guhung Elang Resort Belaban Wilayah-1. Tanaman hias menjadi salah satu objek yang potensial untuk menarik perhatian wisatawan karena keindahan visualnya serta nilai ekologis yang membantu memperkuat keberlangsungan lingkungan. Penelitian ini bertujuan untuk mengeksplorasi potensi flora tanaman hias sebagai objek daya tarik wisata alam di Jalur Patroli Air Terjun Guhung Elang Resort Belaban Wilayah-1 Taman Nasional Bukit Baka Bukit Raya. Penelitian menggunakan metode survei untuk mengeksplorasi keanekaragaman flora tanaman hias yang ada di sekitar area wisata. Titik awal jalur di pusat informasi kantor resort Belaban. Terdapat 2 jalur pengamatan, yaitu jalur 1 (jalur patroli Guhung Elang Km 37) dan jalur 2 (jalur air terjun Semunga Km 35). Parameter penelitian adalah jenis tanaman, titik koordinat, jarak tempuh, dan waktu tempuh. Hasil penelitian menemukan bahwa terdapat potensi tanaman hias sebanyak 20 famili pada kedua jalur, dengan total individu sebanyak 94. Pada jalur 1 terdapat 44 individu, sementara di jalur 2 terdapat 50 individu. Jenis tanaman hias yang paling umum adalah anggrek, senthe/keladi, dan nampu/murau. Temuan potensi flora tanaman hias ini memberikan peluang untuk pengembangan wisata alam di area tersebut dengan menggarap keindahan visual dan nilai ekologis tanaman hias, dapat menarik minat wisatawan untuk mengunjungi lokasi tersebut.Kata kunci: Flora, Potensi, Tanaman Hias, Guhung Elang